HEALTH EDUCATION METHODS AND MANAGEMENT OF INVESTIGATION INFECTIONS OF ACUTERESPECTS (ISPA) - Widaningsih, Widaningsih (Indonesian Journal of Nursing Health Science, 2018)
Health educationis a profession that educates people about health. Areas within the profession include environmental health, physical health, social health, emotional health, intellectual health, and spiritual health. Kebon Jeruk isone of the sub-districts in the Jakarta Capital City Special Region (DKI) which is known that the highest disease occurring in the Kebon Jeruk sub-districtin 2016 is the majority of acute respiratory infections (ISPA) of 61. 7%. Acute Respiratory Infection (ISPA) is a disease that is often encountered with mild to severe manifestations. ISPAâs that affect the lung tissue or severe ISPAâs, maybe come pneumonia. This study aims to analyze the factors causing ISPA and find the right health education method in the management of ISPA problem in Puskesmas Kecamatan Kebon Jeruk with personal approach. The research design used was cross sectional with a large sample of 100 respondents taken through accidental sampling technique. The result of spearman rank correlation test found that on house dwelling density value p-value 0,021 <Î± 0,05 means the reis correlation/relation between density of house occupancy with the incidence of ISPA, and on knowledge level factor p-value 0,001<Î± 0,05 means there is a correlation/relationship between the level of knowledge of the respondent about the management of ISPA with the incidence of ISPA. The conclusion obtained that the factors causing the incidence of ISPA in Puskesmas Kecamatan Kebon Jeruk is the density of dwelling and dirty home environment and the level of knowledge of respondents to the management of the incidence of abad ISPA. Â Keywords: cause factors, ISPA, health education